2013
DOI: 10.1155/2013/459160
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation for the Treatment of Acute Childhood Pneumonia: A Systematic Review

Abstract: Background. Studies have found an increased incidence of vitamin D deficiency in children with pneumonia; however, there is no conclusive data regarding the direct effect of vitamin D supplementation in acute pneumonia. Methods. A comprehensive search was performed of the major electronic databases till September 2013. Randomized controlled trials (RCTs) comparing treatment with vitamin D3 versus placebo in children ≤5 years old with pneumonia were included. Results. Out of 32 full text articles, 2 RCTs includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Peak concentrations of 25(OH)D were found 3 days after bolus administration, which is longer than the time taken for resolution of the clinical features of severe pneumonia (median approximately 30 hours). The findings of Gupta, et al [5] are in keeping with two other studies which reported a lack of a therapeutic effect of acute vitamin D supplementation on the rate of resolution of acute pneumonia [7]. The second aspect of the study by Gupta, et al [5] was to assess the effect of vitamin D supplementation on the incidence of recurrence of pneumonia over six months.…”
supporting
confidence: 67%
“…Peak concentrations of 25(OH)D were found 3 days after bolus administration, which is longer than the time taken for resolution of the clinical features of severe pneumonia (median approximately 30 hours). The findings of Gupta, et al [5] are in keeping with two other studies which reported a lack of a therapeutic effect of acute vitamin D supplementation on the rate of resolution of acute pneumonia [7]. The second aspect of the study by Gupta, et al [5] was to assess the effect of vitamin D supplementation on the incidence of recurrence of pneumonia over six months.…”
supporting
confidence: 67%
“…A systematic review done by Das et al discussed the ineffectiveness of vitamin D in pneumonia comparing two separate randomized trials [20]. One of the trial had used a single dose [12] whereas the other had used multiple doses with daily dosing schedule [19].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown mixed results; while some studies showed evidence of association between vitamin-D status and clinical pneumonia, others did not find any association [35][36][37][38]. A recent systematic review concluded that there was no evidence of therapeutic vitamin D supplementation among under-5 children in the management of clinical pneumonia [39]. This result can be explained by that vitamin-D plays a role in the defense against infection but once infection has taken place, other factors determine its course and whether it will resolve or not.…”
Section: Discussionmentioning
confidence: 99%